Delivery of genes and nucleotides - Yahya, Esam (Henry Stewart Talks, 2023)
Genes and nucleotides, Somatic & germline gene therapy, Gene transfer methods, Physical methods, Chemical methods, Biological method, Vectors used in gene therapy, Diseases studied in gene therapy trials